2020
DOI: 10.1002/er.5298
|View full text |Cite
|
Sign up to set email alerts
|

Thermal runaway behavior and features of LiFePO 4 /graphite aged batteries under overcharge

Abstract: In this paper, the overcharge tests of 25 Ah LiFePO 4 /graphite batteries are conducted in an open environment and the overcharge-to-thermal-runaway characteristics are studied. The effects of current rates (C-rates: 2C, 1C, 0.5C, and 0.3C) and states of health (SOHs: 100%, 80%, 70%, and 60%) on thermal runaway features are discussed in detail. The overcharge process can be summarized into five stages based on the experimental phenomena (C-rate ≥ 1 and SOH ≥ 80%): expansion, fast venting after safety valve rup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…T1 -T3 are located on the same surface, and T4 is located in the center of the other largest surface of the battery. Four pressure sensors are used to record the overpressure generated by the battery explosion, and the pressure sensors are arranged at 150 mm in the horizontal direction and 150 mm in the vertical direction of the battery, which is the same as Literature [6].…”
Section: Battery Samplementioning
confidence: 99%
See 2 more Smart Citations
“…T1 -T3 are located on the same surface, and T4 is located in the center of the other largest surface of the battery. Four pressure sensors are used to record the overpressure generated by the battery explosion, and the pressure sensors are arranged at 150 mm in the horizontal direction and 150 mm in the vertical direction of the battery, which is the same as Literature [6].…”
Section: Battery Samplementioning
confidence: 99%
“…About 0.5 s after the explosion, due to the deflagration, the pressure wave appeared at a second peak (about 46 kPa), which was lower than the first peak pressure. In the early stage, we also studied the pressure wave of the explosion and combustion of the battery under overcharge at 1C [6]. The results showed that the peak pressure of the explosion was also around 100 kPa, while the overpressure caused by the deflagration was around 150 kPa (higher than the explosion pressure wave), indicating that the combustion caused by overcharge (1C) is more intense than that caused by overheating (200 W).…”
Section: Explosion Process and Overpressure Of 100% Soh Batterymentioning
confidence: 99%
See 1 more Smart Citation
“…Aer the cells were fully charged ($100% SOC, stage II), the cathode was fully delithiated and no more Li-ions could be extracted, so the voltage of the battery increased until overcharge reactions initiated, at around 4.7 V, and the continuation of the overcharge reactions produced a voltage plateau of around 5.7 V. The behaviour of the batteries with and without the PTCR lm is similar in these two stages and it is also in good agreement with previous studies on overcharge tests of lithium-ion batteries. [70][71][72][73][74] In the following stage III of the overcharge process (Fig. 6a), the cells with and without the PTCR lm showed totally different overcharge behaviours.…”
Section: Improving the Safety Of Lithium-ion Batteries Under Abuse Co...mentioning
confidence: 99%
“…Lithium‐ion batteries (LIBs) with relatively high power density, inherent high energy density, long cycle life, and eco‐friendly property are considered as a prospective power source for new energy vehicles (NEVs), especially for electric vehicles (EVs) 1‐4 . The energy density is the critical parameter inextricably linked to the driving range of EVs.…”
Section: Introductionmentioning
confidence: 99%